Detection of 3D Spatial-Temporal Spectrum Opportunity in Satellite-Terrestrial Integrated Network - Ning YANG; Daoxing GUO (天地一体化信息网络)
The detection of 3D spectrum opportunities in the downlink sharing scenario in satellite-terrestrial integrated networks was investigated.First, defined the 3D space-time spectrum opportunities in the satellite-terrestrial integrated networks, and further divided the opportunities into three areas in the spatial domain: the communication area of primary user, the communication protection belt, and the free access area.Then, based on the proposed 3D opportunity model, derived the closed expressions of the detection and false alarm probability at the user-level and the network-level, respectively.In order to further utilized the spatial spectrum opportunity, a power control scheme of the cognitive user was determined through 3D spectrum sensing, i.e., interference constraint (IC).The simulation results demonstrated that the proposed power control scheme could realized the detection of 3D spectrum opportunity.